Centralism in the 2004 Constitution of Afghanistan (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
Throughout its history, Afghanistan has lacked a system of separation of powers with checks and balances. Even the 2004 constitution, which was drafted in a relatively open political environment, fell short of establishing such a system. It granted the president excessive executive, legislative, and judicial powers, effectively concentrating power in the executive branch. This centralism fostered autocratic tendencies. The President intervened in legislative matters, bypassing constitutional requirements and weakening legislative oversight. Similarly, the president’s excessive power undermined the independence of the judiciary system, turning it into a tool to pursue his interests. The combined executive, legislative, and judicial powers of the president, coupled with weak oversight institutions, led to unchecked centralism. This concentration of power weakened the rule of law, fueled corruption, exacerbated wealth and power imbalances, and eroded public trust in the government. More importantly, this centralism exacerbated ethnic tensions in the country. The present contribution, informed by the author’s experience with the Constitutional Oversight Commission in Afghanistan, follows a descriptive and analytical approach. It argues that there is a need for decentralizing power in any future constitution in order to establish a modern and stable governance system in Afghanistan.
Keywords: Afghanistan; Constitution; Centralism; Rule of Law; Checks and Balances